The Role of the Ministry of Home Affairs as Non-Military Defense in Handling Inflation to Support National Security - Alexander Lendie Nicholas; Halomoan Freddy Sitinjak Alexandra; Achmed Sukendro; Pujo Widodo; Herlina JR Saragih (Formosa Journal of Social Sciences (FJSS), 2024)
Inflation is one of the non-military threats in the economic dimension, as stipulated in Presidential Regulation Number 8 of 2021 concerning the General Defense Policy of 2020-2024. The Ministry of Home Affairs plays a crucial role as a key component in non-military defense against the threat of inflation in Indonesia. This research aims to elucidate the role of the Ministry of Home Affairs as part of non-military defense in handling inflation to support national security of a country. The author employs a qualitative research method with data collection techniques including interviews, observations, literature review, and data analysis using an interactive model by Miles Huberman, Saldana (2014), and Bruce J. Cohen's Theory of Roles (1992). The research findings indicate that the Ministry of Home Affairs, as part of Non-Military Defense, has played an enacted role in concrete efforts to control inflation. In the context of National Security, these follow-up actions by the Ministry of Home Affairs can have implications for economic stability and the inflation rate to support or maintain national security of a country